Effectiveness of Some Chemical Pesticides Against Arthropod Pests of Ornamental Plant (Bangladesh Journal of Agricultural Research, 2022)
The study was conducted with seven chemical pesticides to control the arthropod pests of some ornamental plants during November 2017 to May 2018 at Gazipur in Bangladesh. Pesticides were applied following company recommended dose, more than recommended dose, farmers’ practicing dose and below farmers’ practicing dose. The pesticides Actara 240SC (Thiamethoxam) and Abom 1.8EC (Abamectin) were applied @ 1.0, 1.25 (farmers’ practice), 1.5 (recommended) and 1.75 ml/L water on rose plants to control aphid and spider mite. Effectiveness of Roxin 40 EC (Dimethoate) @ 0.5, 0.75 (farmers’ practice), 1.0 (recommended) and 1.25 ml/L water was evaluated against aphid attacking tuberose. Actara 25 WG (Thiamethoxam) @ 0.1, 0.2(farmers’ practice), 0.25 (recommended) and 0.3 g/L water was sprayed to control marigold aphid. Tundra 20 SP (Acetamiprid 20%) was sprayed to control rose thrips @ 0.25, 0.5 (farmers’ practice), 0.75 (recommended) and 1.0 g/L water. Effectiveness of Liquor 1.8 EC (Abamectin) against gladiolus thrips was tested @ 1.75, 2.0 (farmers’ practice), 2.5 (recommended) and 2.75ml/L water. Feniton 50 EC (Fenitrothion) was applied to control dahlia mealy @ 1.5, 1.75 (farmers’ practice), 2.0 (recommended) and 2.5 ml/L water. Abundance of the arthropod pests was compared with control (untreated plant) at 1, 3 and 7 days after treatment. The tested pesticides significantly reduced pest population and the recommended dose of the pesticides revealed higher efficacy than that of farmers’ practice.Bangladesh J. Agril. Res. 45(3): 261-268, September 2020